Climate change impacts of forest conversion: Study on forest conversion for food estate (National Food Granary Program) in Central Kalimantan - Pangestu, Jessica Elshad Pramesti; Habib, Syaiful (Interaction, Community Engagement, and Social Environment, 2024)
Background: The Food Estate policy or national food granary program is a food development concept that is integrated with agriculture, plantations and animal husbandry, one of which is in the area of openings in natural forests covering an area of 156,000 ha in Central Kalimantan. This program is designed to prepare national food security in order to respond to the Food and Agriculture (FAO) Report on the threat of a global food crisis due to the impact of the Covid 19 pandemic. Changes in forest cover from previously green land to agricultural land will cause loss of forest cover in the form of vegetation or trees that have ecosystem services as carbon dioxide absorbers from the air. Methods: The impact of forest conversion is analyzed by conducting spatial analysis of land cover and calculating potential carbon stocks lost, as well as providing suggestions or solutions to problems or gaps from an economic, social, and political environmental perspective. Findings: From the results of literature studies, the government must learn from the experience of food estate projects on peatlands in the past where peatlands became thin and when the dry season arrived, the land would be flammable due to lack of attention to the biophysical aspects of the soil. Conclusion: In addition, economic and social aspects involve and assist the community in carrying out food security programs and agricultural technology sophistication. Novelty/Originality of this Study: This analysis provides a unique perspective on the climate change impacts of forest conversion for food estate programs, bridging the gap between national food security policies and environmental conservation imperatives.